Cholinium Cations Enable Highly Compact and Dendrite‐Free Zn Metal Anodes in Aqueous Electrolytes. (22nd May 2022) - Nie, Xueyu; Miao, Licheng; Yuan, Wentao; Ma, Guoqiang; Di, Shengli; Wang, Yuanyuan; Shen, Shigang; Zhang, Ning
Abstract: Metallic Zn is believed to be an ideal anode for aqueous batteries, but its reversibility is deteriorated by noncompact and dendritic Zn deposition along with interfacial parasitic reactions. Herein, it is reported that introducing cholinium (Ch + ) cations into aqueous electrolytes enables a spatially compact, non‐dendritic, and corrosion‐free Zn electrode even at high areal capacity (5.0 and 10.0 mAh cm –2 ) using a pressure‐free electrolytic cell. This strategy is applicable to various Zn‐salt‐based aqueous electrolytes (e.g., 1 M ZnSO4, Zn(CH3 COO)2, and ZnCl2 ). It is found that bulky Ch + cations create a "leveling effect" to homogenize Zn deposition and render an H2 O poor electrical double layer near Zn by favorably absorbing on the Zn surface. Moreover, Ch + cations with –OH group disrupt the original H‐bonded network of water to reduce H2 O‐induced side reactions and promote the Zn 2+ de‐solvation by forming H‐bond with H2 O. As a result, the Zn electrode in the optimized 1 M ZnSO4 with 4 M Ch + electrolyte manifests remarkable electrochemical performances involving high Coulombic efficiency of 99.6% in Zn//Cu cell and prolonged cycling stability over 2000 h in Zn//Zn cell (1.0 mA cm –2, 1.0 mAh cm –2 ). This work provides a new strategy for the design of compact and dendrite‐free Zn battery chemistry. Abstract : Introducing cholinium (Ch + ) cations into aqueous electrolytes can enable a highly compact, non‐dendritic, and corrosion‐free Zn electrode even at high areal capacity (5 and 10 mAh cm −2 ) using a pressure‐free electrolytic cell, because Ch + cations create a "leveling effect", endow an H2 O‐poor electrical double layer near Zn, and break the original H‐bonded network of water.